Perencanaan Dan Pengembangan Sumber Daya Manusia Dalam Meningkatkan Kualitas Pelayanan Kesehatan Di Puskesmas Pauh Kambar - Satria, Benni; Affitra, Muhammad Darrel; Aditya, Rezky; Putra, Ramdani Bayu (Jurnal Ilmiah METANSI ”Manajemen dan Akuntansi”, 2025)
Quality health services are a basic need of the community and are an important factor in the success of national health development. The quality of human resources (HR) is the main element in determining the success of health services. One of the Health Centers in Pauh Kambar, West Sumatra still faces challenges in planning and developing HR. The challenges faced include health workers, low technical competence, suboptimal distribution and managerial and development in the form of training that is still lacking. The purpose of this study was to identify inhibiting and supporting factors in planning and developing HR and their relationship to the quality of health services at the Pauh Kambar Health Center. This study is a descriptive qualitative study with direct interview observation methods and journal literature reviews. The results of the study indicate that there are Human Resource problems at the Pauh Kambar Health Center that affect health services, namely the lack of Human Resource development through training and seminars due to the lack of attention and role of the local government, then the limited budget efficiency factor in developing health worker HR.